The effect of ilmenite viscosity on the dynamics and evolution of an overturned lunar cumulate mantle - Zhang, Nan; Dygert, N.; Liang, Y.; Parmentier, E. (American Geophysical Union, 2017)
Lunar cumulate mantle overturn and the subsequent upwelling of overturned mantle cumulates provide a potential framework for understanding the first-order thermochemical evolution of the Moon. Upwelling of ilmenite-bearing cumulates (IBCs) after the overturn has a dominant influence on the dynamics and long-term thermal evolution of the lunar mantle. An important parameter determining the stability and convective behavior of the IBC is its viscosity, which was recently constrained through rock deformation experiments. To examine the effect of IBC viscosity on the upwelling of overturned lunar cumulate mantle, here we conduct three-dimensional mantle convection models with an evolving core superposed by an IBC-rich layer, which resulted from mantle overturn after magma ocean solidification. Our modeling shows that a reduction of mantle viscosity by 1 order of magnitude, due to the presence of ilmenite, can dramatically change convective planform and long-term lunar mantle evolution. Our model results suggest a relatively stable partially molten IBC layer that has surrounded the lunar core to the present day.